If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (3x + -11) = 10 Reorder the terms: 4x + (-11 + 3x) = 10 Remove parenthesis around (-11 + 3x) 4x + -11 + 3x = 10 Reorder the terms: -11 + 4x + 3x = 10 Combine like terms: 4x + 3x = 7x -11 + 7x = 10 Solving -11 + 7x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 7x = 10 + 11 Combine like terms: -11 + 11 = 0 0 + 7x = 10 + 11 7x = 10 + 11 Combine like terms: 10 + 11 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| 2y^2+y^2=6 | | x^2-520+3x=0 | | 3-(b+3)=5-b | | -6n-3=9 | | 2cos^2=3/2 | | 2y-10x=-4 | | 100-x=x+1 | | 35=7+7x | | 35=7+7c | | 11+2x=3(2-x) | | x+3-2x=35+x | | x+(0.18*x)=160 | | f(x)=2x^2-11x | | 1/(2e^4x) | | 3x+6y=35.3 | | 4j=-8 | | x-7=12x-106 | | 5y-2=47-7 | | 4x^2+6y^2=8 | | 10x-45=3x-55 | | -25+(-57)= | | 7-6x=9x-36 | | 28+(-32)= | | x-15x/100 | | Tn=12+3n | | 12+11=123 | | 3x+34=11x-65 | | (x+2)+ln(x-2)=ln(21) | | 3d=d-7=25/4 | | 3x-x-x+2=13 | | -(2x-3)=-6 | | 6x-3.3=4x-8.3 |